Priming of defense reaction in plants under patogenesis: Induced immunity - Kabashnikova, Liudmila F. (Journal of the Belarusian State University. Ecology, 2021)
The article presents modern ideas about the molecular and cellular bases of systemic acquired resistance (SAR) and induced systemic resistance (ISR) of plants - two forms of induced resistance in which the protective properties of plants are caused by a previous infection or treatment by immunomodulators. The main mechanisms of priming of protective reactions under the pathological process with the participation of natural resistance inducers and ways of their implementation in plants are characterized.
Keywords: phytopathogens; induced immunity; systemic acquired resistance (SAR); induced systemic resistance (ISR); plant resistance inducers; metabolic pathway; priming